2014
DOI: 10.1111/j.1532-950x.2014.12201.x
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo Biomechanical Comparison of V‐Loc 180® Absorbable Wound Closure Device and Standard Polyglyconate Suture for Diaphragmatic Herniorrhaphy in a Canine Model

Abstract: Clinical application of 2-0 barbed polyglyconate suture can be considered as an alternative to the use of 2-0 polyglyconate for diaphragmatic herniorrhaphy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 26 publications
2
19
0
Order By: Relevance
“…In support of our hypothesis, we found that there was no difference in initial leakage pressures between barbed and nonbarbed bladder closures, confirming that the use of barbed suture in an open cystotomy model is as effective as its smooth counterpart. Our findings are consistent with the findings of other studies evaluating the use of barbed suture for diaphragmatic herniorrhapy, gastrotomy and enterotomy closure, skin closure, and canine and equine cystorrhaphy models, showing equivalence when compared to conventional smooth suture.…”
Section: Discussionsupporting
confidence: 91%
“…In support of our hypothesis, we found that there was no difference in initial leakage pressures between barbed and nonbarbed bladder closures, confirming that the use of barbed suture in an open cystotomy model is as effective as its smooth counterpart. Our findings are consistent with the findings of other studies evaluating the use of barbed suture for diaphragmatic herniorrhapy, gastrotomy and enterotomy closure, skin closure, and canine and equine cystorrhaphy models, showing equivalence when compared to conventional smooth suture.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have reported single‐layer or double‐layer closures and have not compared closure types among differing suture types in ovine specimens. Our findings are in line with barbed suture use in other open surgical applications including diaphragmatic herniorraphy, gastrotomy and enterotomy closures in dogs, and porcine cutaneous closure after sharp surgical incision . Conversely, previous studies have shown a significant difference in leakage pressure after cystorraphy when comparing barbed and an equivalent smooth monofilament suture .…”
Section: Discussionsupporting
confidence: 88%
“…In comparison, the bidirectional suture Quill (Angiotech, Vancouver, British Columbia, Canada) is a single cut angle barb. Thus, the barbs in V‐loc 180 are relatively shorter and more rigid, and this geometry could result in a greater tissue holding capacity . We compared the V‐loc 180 to polydioxanone and polyglyconate as they are common sutures used for fascial closure…”
Section: Discussionmentioning
confidence: 99%
“…The absence of a knot is proposed to decrease tissue reaction due to a reduced knot volume and barbed suture has been suggested as an alternative to conventional suture for all soft tissue closures where absorbable suture material is appropriate . Biomechanical studies comparing barbed and monofilament sutures in the dermis, gastro‐intestinal tract, urinary bladder, diaphragm, abdominal wall, and tendon are reported.…”
Section: Introductionmentioning
confidence: 99%